Determinan Nilai Perusahaan: Profitabilitas sebagai Variabel Mediasi di Sektor Makanan dan Minuman - Indah, Nopiani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study investigates the factors influencing firm value within the Indonesian food and beverage industry, specifically highlighting profitability's mediating role. The main goal is to identify the direct and indirect impacts of capital structure, asset growth, and firm size on both profitability and firm value. This quantitative research used a causality approach, analyzing secondary data from the annual financial reports of 48 food and beverage companies listed on the Indonesia Stock Exchange between 2018 and 2022. Data analysis was conducted using eViews 13. The results showed interesting findings: capital structure negatively affected profitability but positively influenced firm value. This suggests there's an optimal way companies should get their funding. Interestingly, asset growth and firm size didn't significantly affect profitability or firm value directly. Furthermore, profitability, as a mediating factor, didn't significantly connect the influence of capital structure, asset growth, or firm size to firm value. These findings imply that how a company's value is created is complex, and other factors, like good management and future opportunities, might be more important.